Pulmonary endarterectomy in chronic thromboembolic pulmonary hypertension: Relationship between treated branches and outcome. (15th April 2023) - D'Armini, Andrea M.; Pin, Maurizio; Celentano, Anna; Te Masiglat, Leslie J.; Borrelli, Ermelinda; Vanini, Benedetta; Klersy, Catherine; Silvaggio, Giuseppe; Monterosso, Cristian; Alloni, Alessia; Pellegrini, Carlo; Ghio, Stefano
Abstract: Background: In patients with chronic thromboembolic pulmonary hypertension (CTEPH) undergoing pulmonary endarterectomy (PEA) it is important to minimize residual obstructions, in order to achieve low postoperative pulmonary vascular resistances and better clinical results. The aim of the study was to test the hypothesis that the greater the number of pulmonary artery branches treated at surgery, the better the hemodynamic and clinical outcome after PEA. Methods: In 564 consecutive CTEPH patients undergoing PEA the count of the number of treated branches was performed directly on the surgical specimens. Post-operative follow-up visits were scheduled at 3 months and 12 months after surgery including right heart catheterization and modified Bruce test. Results: The population was divided into tertiles based on the number of treated branches: Group 1 (from 4 to 30 treated branches, n = 194 patients); Group 2 (from 31 to 43 treated branches, n = 190 patients); Group 3 (from 44 to 100 treated branches, n = 180 patients). At 3 and at 12 months after PEA, after adjustment for confounders, patients in the highest tertile of treated branches had significantly lower values of pulmonary vascular resistance and higher values of pulmonary arterial compliance as compared to the other two groups ( p < 0.002). Hospital mortality was 3% in Group 3, 6% in Group 2 and 10% in Group 1 (overall p = 0.035). Conclusions: In CTEPH patients undergoing PEA, a higher number of treated pulmonary artery branches is associated with a better hemodynamic and a better clinical outcome at 3 months and 12 months after surgery. Highlights: PEA surgery should be aimed at treating as many distal vessels as possible. The higher the number of treated vessels the better the hemodynamic outcome. The higher the number of treated vessels, the better in-hospital and long-term event-free survival The procedure is safe even in most advances patients.